mTOR-mediated nutrient sensing and oxidative stress pathways regulate autophagy: a key mechanism for traditional Chinese medicine to improve diabetic kidney disease - Li, Liu; Zou, Junju; Zhou, Tongyi; Liu, Xiu; Tan, Danni; Xiang, Qin; Yu, Rong (Frontiers in Pharmacology, 2025)
ContextAutophagy plays a pivotal role in the pathogenesis of DKD, and the mechanistic target of rapamycin (mTOR) pathway, which regulates nutrient sensing and oxidative stress responses, is a key regulator of autophagy. Traditional Chinese Medicine (TCM) has garnered attention for its potential to treat DKD by modulating the mTOR signaling pathway, reducing oxidative stress, and restoring autophagic function.ObjectiveThe objective of this study is to examine how mTOR-mediated regulation of nutrient sensing and oxidative stress impacts autophagy in DKD, and to explore how TCM modulates these pathways to improve the condition.MethodsA systematic review was conducted using PubMed, Web of Science, Wanfang Data, and China National Knowledge Infrastructure (CNKI), with the search extended to December 2024. The search subject terms included ‘diabetic kidney disease,’ ‘Traditional Chinese Medicine,’ ‘mTOR,’ ‘nutrient sensing,’ and ‘oxidative stress.’ Studies were rigorously screened by two investigators.ResultsThis review systematically examines the pathogenesis of mTOR-mediated nutrient sensing dysfunction and oxidative stress in DKD, highlighting their impact on autophagy. It further clarifies how these mechanisms are targeted by Chinese medicine in the treatment of DKD. The review summarizes the potential mechanisms by which TCM, including monomers (e.g., Astragaloside IV), individual botanical drugs (e.g., Dendrobium nobile Lindl.), and compound formulations (e.g., Tongluo Digui Decoction), regulate autophagy in DKD through pathways such as AMP-activated protein kinase (AMPK), mTOR, sirtuins (Sirt), and the phosphatidylinositol three kinase (PI3K)/Akt/mTOR signaling pathway. TCM compound formulas share a common foundational framework, with the majority being formulated based on therapeutic principles such as ‘Yiqi’, ‘Yangyin’, ‘Tongluo’, and ‘Huashi’.ConclusionTCM shows promise in treating DKD, with unique advantages in modulating key signaling pathways. However, the underlying mechanisms remain complex and warrant further investigation.